Physics, Buddhism, and Postmodern Interpretation - McCance, Dawne C. (Zygon, 1986)
Abstract. Arguing that the revolution in postmodern physics is concerned essentially not with a change in paradigm but with a change in interpretive standpoint, this paper explores a parallel between the aetiology of disease in Buddhism and the interpretive standpoint introduced by twentieth-century quantum physics. The paper suggests a need to revise central interpretive assumptions of the natural and human sciences, including the traditional projection of an atomistic self.